Residential energy use and energy-saving of older adults: A case from Japan, the fastest-aging country. (May 2021) - Yagita, Yoshie; Iwafune, Yumiko
Abstract: Considering the increased aging population, and the effects of climate change, we examined the energy conservation measures of older adults in Japan, one of the fastest-aging countries in the world, to determine a balance between aging, and low-carbon societies. Although the relationship between aging and energy demands has been previously researched, few studies have identified effective intervention methods for reducing energy consumption in aging societies. We identified the characteristics of older adults' energy consumption, using national statistical surveys and home visit interviews to investigate the context leading to their consumption. The results revealed that older households tend to possess older or larger houses, older housing equipment, and more home appliances. Further, older adults tend to remain in their houses for longer periods, and are less likely to alter their status quo. The results suggest that, the individuals who convey the message might have a greater impact on reducing older adults' energy consumption than the energy consumption information conveyed. Additionally, behavior changes such as housing renovation or relocation should be promoted among early-stage older adults before their cognitive and physical abilities decline.